The contributions of the cooperative teaching strategy in the development of some psychosocial abilities and athletic achievement among pupils (9-10) years in athletics children - brahimi, kaddour; ayad, Mostefa; chenouf, KHALED; ben si kadour, Habib (sports creativity, 2025)
he purpose of this research is to contribute to the cooperative teaching strategy in the development of some psychosocial abilities and athletic achievement in the children (9-10) years in athletics, where we assumed the use of a cooperative teaching strategy contributes to the development of some psychosocial abilities and athletic achievement among students (9-10) ). A year in athletics, where the research sample included 30 elementary school students and were randomly selected. We used some tests (25m sprint, 10-step multiple jump test, wide jump of stability, Running between existing), and b (9-10) years in athletics Children - Need to apply a cooperative teaching strategy to increase the awareness of self-sufficient students and self-learning skills to develop Their talents in various sports activities